The language of disenchantment: Protestant literalism and colonial discourse in British India - Yelle, Robert A. (AAR Reflection and theory in the study of religion, 2013)
Orientalism and the language of disenchantment -- "A disease of language": the attack on Hindu myth as verbal idolatry -- "One step from Babel to Pentecost": colonial codification, universal languages, and the debate over Roman transliteration -- "Vain repetitions": the attack on Hindu mantras -- The Hindu Moses: Christian polemics against Jewish ritual and the secularization of Hindu law